Environmental Sustainability Efforts in Esports Organizations toward Climate Action - Ojala, Arto; Hasanovic, Emir; Hasan, Rakibul (University of Hawaii, 2025)
As the global esports industry continues to grow, concerns regarding its environmental sustainability have garnered increasing attention. However, there is still an apparent lack of research on esports that intersect environmental sustainability, particularly to climate action. Our study aimed to gain a deeper understanding of efforts made by the esports stakeholders to achieve climate action. The findings reinforce the importance of existing United Nations’ climate action framework for esports and highlight the potential for esports organizations to promote greater environmental responsibility.
Keywords: Esports; Climate action; Environmental sustainability; Digitalization; fi=Kansainvälinen liiketoiminta|en=International Business|